Transformasional kepentingan rakyat dalam perspektif pemberdayaan masyarakat bagi penanganan kemiskinan sosial melalui Government Social Responsibility (GSR) - FX Sudjatmoko; Nur Dewi Setyowati (Masyarakat, Kebudayaan dan Politik, 2017)
Poverty is a national problem that still cannot be solved by government until present. One of its causing factor is the inability of related policy to solve essential problems faced by poor society. As the result, there are many social programs which are expected to provide solution to poverty problem. Government Social Responsibility is an approach model in order to build relation toward harmonization between government and society, through effort of knowing and understanding problem that is faced by society directly, so it can be a reference in determining government policy that make closer between government action with public interest. The long-term purpose of this research is to get scientific information, teaching material, and as the guidance for handling social poverty problem. Moreover, this research especially aims to find a new model or concept and/or develop a model for handling poverty. The objects of this study are official bureaucracy or government and society in East Java Province. Through Government Social Responsibility program, it is expected to minimize discrepancy between government interest with society interest, and it is expected that government policy is more oriented to aspiration and broad society interest, so that social programs can be a right solution in effort to overcome poverty.